Synthesis of Novel Highly Functionalized 4-Thiazolidinone Derivatives from 4-Phenyl-3-thiosemicarbazones - Abdelmadjid Benmohammed (Molecules, 2014)
We present herein the synthesis in good yields of two series of highly functionalized thiazolidinone derivatives from the reactions of various 4-phenyl-3-thio-semicarbazones with ethyl 2-bromoacetate and diethyl acetylenedicarboxylate, respectively.